Intracranial Rosai-Dorfman Disease - Yadav Arun Kumar; Peng Yi Peng; Xia Chen Chen (Case Reports in Radiology)
Rosai-Dorfman disease (RDD) is a rare, benign pseudolymphomatous condition, predominantly involving lymph nodes. Rosai-Dorfman disease (RDD) (sinus histiocytes with massive lymphadenopathy) rarely affects the intracranial region without involvement of other sites. It is a rare and idiopathic histoproliferation disorder characterized by painless lymphadenopathy. We report a case of 43-year-old male who presented with unconsciousness; MRI was done and right temporofrontal mass was found. Excision was done, and on histopathology it confirmed RDD.